Rheological Properties of Malted and/or Fermented Faro 44 Rice Plus Soybean-Based Complementary Foods - Bristone, C; Ariahu, C. C.; Ikya, J. K.; Eke, M. O.; Eke, M. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
High nutrient density foods are required by infants for optimal healthy growth. This can be achieved by an established food processing technology. So, the study investigated the rheological properties (concentrations, stress or shear rate, viscosities or consistency indices, activation energies, frequency factors) of rice-based formulated food products as affected by either malting and/or fermentation. FARO 44 rice cultivar was processed, and different flours obtained were further formulated with processed soybean (Glycine max) flour. In each of those mixing ratios, 16% protein (PAG’s recommendations) was obtained by a material balance equation. A digital viscometer was used to measure the viscosities of the gruels at levels of 4 concentrations, 4 shear rates and 6 temperatures. Subsequently, the Power law fluids model, Arrhenius kinetic type equation, and linear regression analysis (at levels of 4 concentrations, 4 shear rates and 6 temperatures) were employed to generate the rheological parameters of the gruels. Results showed that viscosity decreased with an increase in temperature within the 30 - 80 oC range studied and shear rate (6 - 60 rpm.) but increased with an increase in concentration (5 - 20%) of gruels. Regardless of temperature or concentration, the consistency indices (1.68 to 714.32 Nsnm-2) of gruels, and their respective flow behaviour indices (n) and activation energy ranged from 0.01 to 0.43 and 5.25 to 36.97 kJ/mol. All formulated products exhibited pseudoplasticity and sensitivity to temperature change. Malting and/or fermentation showed a significant (p < 0.05) reduction in viscosities and revealed that it can be used to increase the nutrient density required by infants.